Managing operational risks in a bank: applied research in Malaysia / Syed Syafudin Syed Abu Hassan and Rozainun Abdul Aziz - Syed Abu Hassan, Syed Syafudin (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2008)
This paper aims to offer better insights into risk management practices of a bank in order to mitigate its operational risks. Far from closely adopting the requirements and due to the nature of the risks faced by banks, this study investigates and observes how such framework is modified in practice to suit the nature and timing of operational risks. Using the case study approach of investigation, we conducted our study in a bank in Malaysia and examined its risk management processes through interviews, documents and physical observations. The paper highlights the implementation of a risk management program and summarises a record of related practices of how the bank manages its operational risks based on adaptation to Bank Negara Malaysia (BNM) guidelines and the Basel II committee paper. The findings will be useful to other banks to benchmark with their risk management program for enhancement purposes. It will also provide a guide as to how operational risks in a bank are managed effectively.